Using Artificial Intelligence Tools for the Professional Development of Teaching Staf - Kovalenko, Valentyna; Marienko , Maiia; Shyshkina, Mariya; Iatsyshyn , Anna (Educological discourse, 2025)
This article addresses the use of artificial intelligence (AI) tools in the professional development of teaching staff within the context of the digital transformation of education. The growing role of intelligent technologies demands that educators possess a high level of digital competence and the ability to integrate AI into their professional activities. The study combines qualitative and quantitative research methods. A content analysis of international and national scientific publications, legal regulations, and digital education support programs has been conducted. Based on the synthesis of Ukrainian experience, the article analyses educators’ main directions, barriers, and needs regarding integrating AI into their professional development. An analysis of international experience, particularly within the framework of EU regulatory initiatives (such as the AI Act) and studies by foreign authors, indicates a profound transformation in approaches to teacher professional development. AI is increasingly used to create personalized educational pathways, adaptive content, automated assessment, and learning analytics. Ethical, legal, and infrastructural challenges associated with AI implementation are emphasized. A survey of 487 Ukrainian teaching professionals was conducted to assess their level of awareness, frequency of AI tool usage, purposes of application, and self-assessment of digital competences. It was found that most respondents (65.8 %) occasionally use AI in their work, while 28 % mainly apply AI tools for their professional development. At the same time, 57.1 % of educators assessed their AI proficiency as average, and 26.9 % as low. A strong demand for convenient, free, user-friendly tools and scientific and methodological support in AI integration processes was identified. The article also describes activities conducted by the authors between 2023 and 2025, including international conferences, webinars, workshops, and practical sessions attended by over 750 educators. These events aimed to develop skills in modern AI tools for generating texts, images, presentations, and more. The results demonstrated high participant engagement, a desire for continued learning, and readiness to integrate AI into their pedagogical practices.